2020
DOI: 10.3390/foods9121769
|View full text |Cite
|
Sign up to set email alerts
|

A Revisit to the Formation and Mitigation of 3-Chloropropane-1,2-Diol in Palm Oil Production

Abstract: Process-based contaminants in food—particularly in vegetable oils—have been a topic of interest due to their potential health risk on humans. Oral consumption above the tolerable daily intake might result in health risks. Therefore, it is critical to correctly address the food contaminant issues with a proper mitigation plan, in order to reduce and subsequently remove the occurrence of the contaminant. 3-monochloropropane-1,3-diol (3-MCPD), an organic chemical compound, is one of the heat- and process-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 135 publications
0
23
0
Order By: Relevance
“…The residual color content in RBD palm oil was 1.9 ± 0.1 Red below the maximum value (≤3 Red) of refined palm oil color suggested by the Palm Oil Refiners Association of Malaysia [ 22 ]. The degumming process effectively removes the hydroperoxide content in RBD palm oil [ 23 ], which was assigned by reducing PV values in CPO and RBD palm oil ( Table 6 ). The determination of the fatty acid compositions is vital in assessing palm oil’s nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…The residual color content in RBD palm oil was 1.9 ± 0.1 Red below the maximum value (≤3 Red) of refined palm oil color suggested by the Palm Oil Refiners Association of Malaysia [ 22 ]. The degumming process effectively removes the hydroperoxide content in RBD palm oil [ 23 ], which was assigned by reducing PV values in CPO and RBD palm oil ( Table 6 ). The determination of the fatty acid compositions is vital in assessing palm oil’s nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that other research has shown that certain metal ions, and particularly Fe 3þ and Fe 2þ , enhance the formation of 3-MCPD when vegetable oil is heated. 49 With heating to 400 C and addition of 1 g of either Al 2 O 3 , Fe 2 O 3 , or CuO, there were increases in the levels of PCDD/Fs detected in the smoke. No significant amounts of PCDD/Fs were detected when sucralose was heated in the presence of the metal oxides at 300 C. In general, these studies are effectively pyrolysis studies, which do not represent conditions during normal food manufacture.…”
Section: -Mcpdmentioning
confidence: 94%
“…One of the main disadvantages is the loss of substances responsible for healthy, pharmaceutical properties and technological interest in the oils, such as tocopherols, phospholipids, squalene, polyphenols, and phytosterols [ 5 , 18 ]. Another notable disadvantage of refining is the formation of undesirable compounds such as glycidyl ester, 3-MCPD-esters [ 19 ], harmful trans-fatty acids [ 5 , 20 ], and polymeric triacylglycerols [ 21 ]. These can directly influence the safety level of refined oils.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, such refining process for crude oils should be undertaken with the aim of removing undesirable compounds and avoiding the least possible damage to desirable components [ 14 , 23 ]. It is also important to minimize oil and generate less levels of harmful compounds such as 3-MCPD-esters [ 19 , 23 ] and unhealthy trans-fatty acids [ 5 ]. Some review articles were devoted to describing refining process and technology involved as well as its effects on refined vegetable oils with an emphasis on chemical composition [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%